2010
DOI: 10.17221/113/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Selenium biofortification and antioxidant activity in lettuce plants fed with selenate and selenite

Abstract: Selenium is an important element associated with enhancement of antioxidant activity in plants, microorganisms, animals, and humans. In Brazil, the information on Se in agricultural crops is lacking, though there are indications that low levels of Se are consumed by the population. The experiment was conducted under greenhouse conditions with pots containing 3 l of nutritive solution in a completely randomized factorial design, with seven Se concentrations (0, 2, 4, 8, 16, 32, and 64 µmol/l) and two forms of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
79
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 28 publications
(23 reference statements)
20
79
1
7
Order By: Relevance
“…1 and 2) was described by other authors, such as Xu et al (2003), Hajiboland and Amjad (2007), Ramos et al (2010) and Becvort-Azcurra et al (2012) (Fig. 1).…”
Section: Sesupporting
confidence: 74%
See 1 more Smart Citation
“…1 and 2) was described by other authors, such as Xu et al (2003), Hajiboland and Amjad (2007), Ramos et al (2010) and Becvort-Azcurra et al (2012) (Fig. 1).…”
Section: Sesupporting
confidence: 74%
“…The quantities of Se 4+ applied in the nutrient solution and with the foliar spray are high but did not exceed those used by Becvort-Azcurra et al (2012) and Xue et al (2001), who, along with Ramos et al (2010), reported a positive effect of Se on vegetable growth (Table 1).…”
Section: Discussionmentioning
confidence: 62%
“…The Cys content decreased with the increasing rate of selenite (SeO 3 2-) application and increased with the increasing rate of selenate (SeO 4 2-) application. Ramos et al (2010) described different effects of various forms of Se on the metabolism of lettuce plants (Lactuca sativa L.). These results imply that the response of Cys metabolism to Se is the result of a combination of effects determined by plant species, variety and form of applied Se.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike mammals, Se is not a plant nutrient although is considered a beneficial element that have the potential to influence the antioxidant activity systems of the higher plants (Pilon-Smits and Quinn, 2010;Ramos et al, 2010). However, excessive content of Se in plant tissue may be detrimental for most crops (Terry et al, 2000).…”
Section: How To Increase Selenium Intake By Humansmentioning
confidence: 99%
“…In addition, agronomic biofortification refers to the use of Se-containing fertilizers (applied to soil and/or by foliar spray) to increase contents of Se in staple plant foods. Genetic and agronomic biofortification of staple crops have been extensively studied and have showed to be good approaches to increase the natural intake of Se by animals and humans (Pilon-Smits and Quinn, 2010;Ramos et al, 2010;Fairweather-Tait et al, 2011;Ávila et al, 2013).…”
Section: How To Increase Selenium Intake By Humansmentioning
confidence: 99%